The beneficial effects of a gas-permeable flask for expansion of Tumor-Infiltrating lymphocytes as reflected in their mitochondrial function and respiration capacity. (1st February 2016) - Forget, Marie-Andrée; Haymaker, Cara; Dennison, Jennifer B; Toth, Christopher; Maiti, Sourindra; Fulbright, Orenthial J; Cooper, Laurence J N; Hwu, Patrick; Radvanyi, Laszlo G; Bernatchez, Chantale
Abstract : Adoptive transfer of autologous ex vivo expanded tumor-infiltrating lymphocytes (TIL) is a highly successful cell therapy approach in the treatment of late-stage melanoma. Notwithstanding the success of this therapy, only very few centers worldwide can provide it. To make this therapy broadly available, one of the major obstacles to overcome is the complexity of culturing the TIL. Recently, major efforts have been deployed to resolve this issue. The use of the Gas-permeable flask (G-Rex) during the REP has been one application that has facilitated this process. Here we show that the use of this new device is able to rescue poor TIL growth and maintain clonal diversity while supporting an improved mitochondrial function.